ANALYSIS OF THE INFLUENCE OF CONSUMER BEHAVIOR ON THE DECISION OF APPLYING MULTI-PURPOSE LOANS IN FINANCIAL TECHNOLOGY (FINTECH) - Sukma Irdiana; Kusnanto Darmawan; Kurniawan Yunus Ariyono; Yulian Ade Chandra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to analyze the effect of consumer behavior on the decision to submit a multipurpose loan for funds in the science and technology sector. The sample used in this study was 80 respondents. By using the accidental sampling method. The data used are primary data using questionnaires. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it can be seen that there is a significant influence of cultural and social factors on the decision to submit a multipurpose fund loan to the science and technology department. While there is no significant effect of personal factors on the decision to apply for a multipurpose fund loan in fintek, while the adjusted R Square value obtained is 0.525. This shows that the amount of cultural, social and personal contribution simultaneously influences the decision to apply for a multipurpose fund loan in fintek is 52.5%, while the remaining 47.5% is influenced by factors outside cultural, social and personal.